Morphology of 137 Fast Radio Bursts Down to Microsecond Timescales from the First CHIME/FRB Baseband Catalog - Ketan R. Sand; Alice P. Curtin; Daniele Michilli; Victoria M. Kaspi; Emmanuel Fonseca; Kenzie Nimmo; Ziggy Pleunis; Kaitlyn Shin; Mohit Bhardwaj; Charanjot Brar; Matt Dobbs; Gwendolyn M. Eadie; et al. (The Astrophysical Journal)
We present a spectro-temporal analysis of 137 fast radio bursts (FRBs) from the first CHIME/FRB baseband catalog, including 125 one-off bursts and 12 repeat bursts, down to microsecond resolution using the least-squares optimization fitting routine fitburst . We measure subburst components within burst envelopes as narrow as ~23 μ s (FWHM), with 20% of the sample displaying substructures narrower than 100 μ s, offering constraints on emission mechanisms. Scattering timescales in the sample range from 30 μ s to 13 ms at 600 MHz. Our measured values are compared with those in the first CHIME/FRB intensity catalog, revealing that nearly one-third of our sample exhibits additional burst components at higher time resolutions. We observe no correlations between scattering time and dispersion measure, rotation measure, or linear polarization fraction, with the latter suggesting that depolarization due to multipath propagation is negligible in our sample. Bursts with narrower envelopes (≤1 ms) in our sample exhibit higher flux densities, indicating the potential presence of submillisecond FRBs that are being missed by our real-time system below a brightness threshold. Most multicomponent bursts in our sample exhibit subburst separations of ≤1 ms, with no bursts showing separations < 41 μ s, even at a time resolution of 2.56 μ s, but both scattering and low signal-to-noise ratio can hinder the detection of additional components. Lastly, given the morphological diversity of our sample, we suggest that one-off and repeating FRBs can come from different classes but have overlapping property distributions.